Description of steady-state creep rate with continuously varying stress sensitivity parameter and upper limits of applied stress - Jan Kohout (Heliyon)
The steady-state creep rate increases with working temperature according to the Arrhenius law and with applied stress according to the power law. The dependence on both the variables is usually expressed as the product of the Arrhenius law and the power law, where a constant value of the apparent activation energy is assumed. As the exponent of the power law, called the stress sensitivity parameter and dependent on the deformation micromechanism, a specific integer is taken. A deeper study of empirical results shows that the apparent activation energy depends significantly on the applied stress and the deformation mechanism can change if the temperature varies over a wide range. Taking these two facts into account, a new equation for the dependence of the steady-state creep rate on the working temperature and on the applied stress was derived and verified using real creep measurement results. Moreover, the convexly bent curves representing the dependence of the creep rate on the applied stress in bilogarithmic plot do not need to be described using the questionable sinhx function, but it is sufficient to assume the existence of upper limits of the applied stress leading to immediate fracture.